2022
DOI: 10.1182/bloodadvances.2021006909
|View full text |Cite
|
Sign up to set email alerts
|

Using stroma-anchoring cytokines to augment ADCC: a phase 1 trial of F16IL2 and BI 836858 for posttransplant AML relapse

Abstract: Natural killer (NK) cells are key effectors in cancer immunosurveillance and posttransplant immunity, but deficiency of environmental signals and insufficient tumor recognition may limit their activity. We hypothesized that the antibody-mediated anchoring of interleukin-2 (IL-2) to a spliced isoform of the extracellular matrix (ECM) glycoprotein tenascin-C would potentiate NK cell-mediated antibody-dependent cellular cytotoxicity (ADCC) against leukemic blasts. In this novel-novel combination, dose-escalation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Quantitative biodistribution studies have shown that those radiolabeled immunocytokines directed against the EDB domain of fibronectin preferentially localize to the tumor without being trapped in blood or secondary lymphoid organs (Erba et al, 2012 ; Poli et al, 2013 ). Encouraging clinical evidence of exceptional therapeutic activity is emerging in certain indications such as metastatic melanoma (Eigentler et al, 2011 ; Weide et al, 2014 ; Danielli et al, 2015 ), high-risk basal cell carcinoma ( NCT03567889 ), glioblastoma (Look et al, 2023 ) and acute myeloid leukemia (Berdel et al, 2022 ). The use of antibody fragments as delivery vehicles is particularly attractive, as they may facilitate a preferential uptake in the neoplastic lesion while being rapidly cleared from the circulation (Carnemolla et al, 2002 ; Halin et al, 2002 ; Borsi et al, 2003 ; De Luca et al, 2017 ; Ongaro et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative biodistribution studies have shown that those radiolabeled immunocytokines directed against the EDB domain of fibronectin preferentially localize to the tumor without being trapped in blood or secondary lymphoid organs (Erba et al, 2012 ; Poli et al, 2013 ). Encouraging clinical evidence of exceptional therapeutic activity is emerging in certain indications such as metastatic melanoma (Eigentler et al, 2011 ; Weide et al, 2014 ; Danielli et al, 2015 ), high-risk basal cell carcinoma ( NCT03567889 ), glioblastoma (Look et al, 2023 ) and acute myeloid leukemia (Berdel et al, 2022 ). The use of antibody fragments as delivery vehicles is particularly attractive, as they may facilitate a preferential uptake in the neoplastic lesion while being rapidly cleared from the circulation (Carnemolla et al, 2002 ; Halin et al, 2002 ; Borsi et al, 2003 ; De Luca et al, 2017 ; Ongaro et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the targeted delivery of IL2, TNF, and IL12 led to a potentiation of the cytokine payload as a result of increased density and activity of tumor resident T cells and NK cells, capable of neoplastic cell recognition (Halin et al, 2002 ; De Luca et al, 2017 ; Puca et al, 2020 ; Weiss et al, 2020 ; Look et al, 2023 ). Immunocytokines based on these payloads have progressed to late-stage clinical trials with promising results in difficult-to-treat cancer indications, including metastatic melanoma (Eigentler et al, 2011 ; Weide et al, 2014 ; Danielli et al, 2015 ), high-risk basal cell carcinoma ( NCT03567889 ), glioblastoma (Look et al, 2023 ) and acute myeloid leukemia (Berdel et al, 2022 ). Our group has worked extensively on cytokine fusions based on the fully human L19 antibody, specific to the alternatively spliced EDB domain of fibronectin.…”
Section: Introductionmentioning
confidence: 99%
“…As previously stated, IT applied to AML comprises checkpoint inhibitors (anti-PD-1, anti-PD-L1, anti-CTLA-4), T cells genetically redirected to leukemia cells (CAR-T therapies), antibodies against tumor antigens (GO, anti-CD33 antibodies), NK cell-based therapies, among others [ 78 , 79 , 80 , 81 , 82 , 83 ]. Additionally, other therapies, such as those based on anti-AML vaccines, are under clinical study [ 84 , 85 , 86 ].…”
Section: Dendritic Cells and Acute Myeloid Leukemiamentioning
confidence: 99%
“…BDNF, brain derived neurotrophic factor; BMPs, Bone morphogenetic proteins; CALEB, chicken acidic leucine-rich EGF-like domain containing brain protein; CNTN1, Contactin-1; CTGF, connective tissue growth factor; EGF, Epidermal growth factor; EGFR, EGF receptor; FBG, Fibrinogen-like globe; FN, Fibronectin; FNIII, Fibronectin type III; HB-EGF, heparin-binding EGF-like growth factor; FGF, fibroblast growth factor; HGF, hepatocyte growth factor; HSP33, heat shock protein 33; IGF, insulin-like growth factor; NaN, sodium channel subunit β2; NGF, Nerve growth factor; NT-3, Neurotrophin-3; PDGF, Platelet-derived growth factor; PIGF, placental growth factor; RPTPβ, receptor protein tyrosine phosphatase β; TA, Tenascin assembly; TGFβ, Transforming growth factor β; TLR4, toll-like receptor-4; VEGF, vascular endothelial growth factor. The information taken and modified from Refs 11 - 22 .…”
Section: Figurementioning
confidence: 99%